Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.

Use Coupon: CART20 and get 20% off on all online Study Material

Total Price: Rs.

There are no items in this cart.
Continue Shopping

Solved Examples on Differential Equations

Illustration 1: The differential equation dy/dx = √(1-y2)/y determines a family of circle with:

1. variable radii and  affixed centre at (0, 1)

2. variable radii and  affixed centre at (0, -1)

3. fixed radius 1 and variable centres along the x-axis

4. fixed radius 1 and variable centres along the y-axis

Solution: The given equation is

dy/dx = √(1-y2)/y

Taking the terms of y and x on separate sides

y/√(1-y2)dy = dx

Integrating both sides, we get

∫y/√(1-y2) dy = ∫dx

-√(1-y2) = x + c

Hence, we get x2 +y2 + 2cx + c2 - 1 =0

or 1- y2 = (x + c)2

This clearly shows that this differential equation represents a circle of fixed radius 1 and variable centres along x –axis.

Get Chapter Test for this Topic

Illustration 2:Solve (D2 + 4) y = x sin2x.

Solution:The C.F can be easily obtained as C.F.  = c1cos 2x + c2 sin2x

P.I. = 1/ (D2+4). x sin 2x

       = {x- 1/(D2+4) .2D}. 1/(D2+4). sin 2x

= {x- 1/ (D2+4). 2D}{-x/4 cos 2x}

= -x2/4 cos 2x + ½.1/(D2+4) (cos 2x- 2x sin 2x)

= -x2/4 .cos 2x + ½ 1/(D2+4) cos 2x – 1/(D2+4) x sin 2x

= -x2/8 cos 2x +1/16 x sin 2x

So, y= c1cos 2x + c2 sin 2x – x2/ 8 cos 2x + 1/16 x sin 2x.

Illustration 3:Solvecos (x+y+1) dx- dy = 0

Solution: Rearranging the terms it can easily be reduced to variable separable.

So, dy / dx= cos (x+y+1)

If we substitute t = x+y+1, we get

dt/ dx = 1+ dy/dx

So, dy/dx = (dt/dx)-1.

Hence the equation becomes, (dt / dx) -1 = cos t

So, dt / dx = 1+ cos t

Now taking the terms of t on one side and of x on the other

dt / (1+cos t) = dx ……(1)

For integrating (1+cos t), first we write it as 2 cos2t/2 using the formula cos 2x = 2 cos2x-1.

Now integrating dt/ 2cos2 (t/2) i.e. ½ sec 2 (t/2) gives tan t/2. So, using this in equation (1) we get

tan t/2 – x = c

Hence, tan [(x+y+1)/2] –x = c.


Upto 50% Scholarship on Live Classes

Course Features

  • Video Lectures
  • Revision Notes
  • Previous Year Papers
  • Mind Map
  • Study Planner
  • NCERT Solutions
  • Discussion Forum
  • Test paper with Video Solution